Crystallization kinetics of Bi1.7V0.3Sr2Ca2Cu3Ox glass-ceramic - Koralay, H; Yakuphanoğlu, Fahrettin; Cavdar, S; Günen, A; Aksu, E (Elsevier Science Bv, 2005)
Crystallization kinetics of Bi1.7V0.3Sr2CaCu3Ox glass-ceramic was investigated using the differential scanning calorimetry (DSC) technique. Three characteristic phenomena were observed in the studied temperature range. The activation energies for glass transition temperature and crystallization phenomena were determined by different theoretical models. Applying the modified Johnson-Mehl-Avrami (JMA) equation reasonably suggests that crystallization process of the Bi1.7V0.3Sr2Ca2Cu3Ox glass-ceramic is carried out by a bulk growth in three dimensions. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: glass-ceramic; crystallization kinetics; Avrami parameter; glass transitions